Letter (copy) : Goods for Northern Spain - Bell, Ernest A.
029-0131-001 40 Bales Dried Cod 63 63 9 Tons Sugar 72.15 64.12.0 10 cwt Irish Middles 44 44 3 cwt cornflour 5.11 5.11 10 sacks Flour 57.15 48.2.6 Tomas Miners' Union Gijon TMU. West Hartlepool 16 Tons 292/946/29/131